Screening of potential endoglucanases, hydrolysis conditions and different sugarcane straws pretreatments for cello-oligosaccharides production - Barbosa, Fernando César; Martins, Manoela; Brenelli, Lívia Beatriz; Ferrari, Felipe Augusto; Forte, Marcus Bruno Soares; Rabelo, Sarita Cândida [UNESP]; Franco, Telma Teixeira; Goldbeck, Rosana (Elsevier, 2020)
Cello-oligosaccharides (COS) are oligomers with 2 to 6 β-1,4-linked glucose units, with potential applications in the food/feed and bioenergy industrial sectors. In this study, the combination of five heterologous expressed endoglucanases varying the temperature and pH conditions were evaluated by design of experiments for COS production. Afterwards, the best combination was tested to produce COS from different pretreated sugarcane straws: ionic liquid, diluted acid, hydrothermal and steam-explosion. The results showed that steam explosion pretreated sugarcane straw treated with CtCel9R enzyme at 50 °C and pH 5.0 yielded 13.4 mg COS g biomass−1, 5–18-fold higher compared to the other pretreated straws. Under the conditions evaluated, the removal of hemicellulose and decrease in the cellulose crystallinity can benefits the enzymatic hydrolysis. This is the first study that combined the evaluation of different enzymes, conditions, and sugarcane straw pretreatments to optimize COS production in a single step without glucose formation.
Keywords: Cello-oligosaccharides; Endoglucanases; Hydrolysis; Pretreatment; Sugarcane straw